Epibiotic barnacles (Crustacea: Cirripedia: Thoracica) collected by the Kumejima 2009 Expedition, with descriptions of two new species - Chan, Benny K. K.; Hayashi, Ryota (Zootaxa, 2012)
The present study reports on the epibiotic barnacles collected by the Kumejima 2009 Expedition. Six cirripedespecies from five genera within four families were identified: Oxynaspis celata Darwin, 1852, Euscalpellum c.f.squamosum Hiro, 1937, Poecilasma obliqua (Hoek, 1907) and Platylepas hexastylos (Fabricius, 1798), all ofwhich had been recorded previously from Japanese waters, and two new taxa, Calantica arcuata n. sp. andOxynaspis ryukyuensis n. sp. The hosts of the barnacles collected included antipatharian corals, gorgonian corals, a decapod crustacean and a sea turtle.